Possible involvement of nerve growth factor in dysmenorrhea and dyspareunia associated with endometriosis - Kajitani, Takashi; Oda, Hideyuki; Uchida, Sayaka; Asada, Hironori; Maruyama, Tetsuo; Miyazaki, Kaoru; Ono, Masanori; Uchida, Hiroshi; Arase, Toru; Yoshimura, Yasunori (Endocrine Journal, 2013)
Nerve growth factor (NGF) has been recently proposed as one of the key factors responsible not only for promotion of nerve fiber growth but also for the onset and maintenance of pain in a variety of diseases. The aim of this study was to investigate the role of NGF in the pelvic pain associated with endometriosis. Tissue and peritoneal fluid samples were collected from 95 women with laparoscopically and histopathologically confirmed endometriosis and 59 control women without endometriosis. Expression levels of NGF mRNA and protein were examined using real-time RT-PCR and immunohistochemistry, respectively. Concentration of NGF in the peritoneal fluid (PF-NGF) was measured using ELISA. The degree of dyspareunia and dysmenorrhea was evaluated using a verbal rating scale. Real-time RT-PCR analysis revealed that NGF mRNA was significantly more abundant in the ovarian endometriomas and peritoneal endometriosis than in the normal control endometrium. Immunohistochemical analyses demonstrated that NGF was prominently expressed and preferentially localized to the glands of the ovarian endometriomas and peritoneal endometriosis, whereas it was only weakly detectable in the normal endometrium. Although PF-NGF was undetectable in some normal subjects and endometriosis patients, elevated PF-NGF in the peritoneal fluid was more frequently observed in endometriosis patients with severe pain than in those with less severe pain. Our results suggest that NGF produced locally in the peritoneal cavity may be involved in the generation of endometriosis-associated pelvic pain.